2016
DOI: 10.1016/j.rmed.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Real life data on incidence and risk factors of severe asthma exacerbations in children in primary care

Abstract: Real-life data on the incidence rates (IR) and risk factors of severe asthma exacerbations in children are sparse. We aimed to assess IR and risk factors of severe asthma exacerbations in children in real life. We conducted a population-based cohort study using a Dutch GP database containing complete medical records of >1 million patients. All records of children with physician-diagnosed asthma aged 5-18 years between 2000 and 2012 were examined for exacerbations, defined as either hospitalization, emergency d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
1
30
0
2
Order By: Relevance
“…In this study, most of the pa ents were found to have taken asthma medica ons in the past year which was consistent 13 with findings of other studies as well. Most of the pa ents were found to have been given salbutamol and/ or oral steroids by their parent for cough.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, most of the pa ents were found to have taken asthma medica ons in the past year which was consistent 13 with findings of other studies as well. Most of the pa ents were found to have been given salbutamol and/ or oral steroids by their parent for cough.…”
Section: Discussionsupporting
confidence: 92%
“…Children who exacerbated made up 32% of our wheezing population, which is similar to other UK cohorts. Non‐UK cohorts showed either lower or higher exacerbation rates, although some of the studies reporting higher exacerbation rates were carried out in high‐risk populations with preponderance of severe asthmatics …”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our study is that we do not have a replication popu- population, which is similar to other UK cohorts. Non-UK cohorts showed either lower 3,30 or higher 31 exacerbation rates, although some of the studies reporting higher exacerbation rates were carried out in high-risk populations with preponderance of severe asthmatics. 31 We acknowledge that there may be an underestimation of severe exacerbations among pre-school children as a consequence of a relatively stringent definition we used, and we cannot exclude the possibility that the underestimation of severity may be more likely requiring the use of oral and/or injectable corticosteroids-that is the phenotype which we focussed on relates to genuinely severe exacerbations.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…The strongest clinical predictor of a general risk for future asthma attacks remains a previous asthma attack: 25% of children with a previous asthma attack had at least one subsequent asthma attack in the following 12 months. 73 In an attempt to summarize this clinical risk, the Asthma Exacerbation Clinical Score (ECS)-ascertained from 17 questions in the four domains of symptoms, medication, healthcare utilization, and medical history-was validated in a cross-sectional study and evaluated using data from the Childhood Asthma Management Program (CAMP). ECS was able to predict asthma attacks up to 1 year later with a sensitivity of 0.69; therefore, it may be a helpful tool in patients with increased risk.…”
Section: Predicting Patients At Risk Of An Asthma Attackmentioning
confidence: 99%